Sistem Pendukung Keputusan Pemilihan Media Sosial Sebagai Media Pemasaran di Manokwari Menggunakan Metode Weighted Product (WP): Decision Support System for Choosing Social Media as Marketing Media in Manokwari Using the Weighted Product Method) - Eva Anjuni; Lion Ferdinand Marini; Christian Dwi Suhendra (Universitas Papua, 2023)
Social media users get their own convenience in marketing their products through the internet because they can increase sales with not too much expenditure. Therefore, the purpose of this study is to choose which social media is often used as marketing media in Manokwari using a decision support system with the weighted product (WP) method. The selection of social media in this study is Tiktok, Instagram, Facebook, and Whatsapp and has criteria such as desire, easy to understand, income, and marketing. Data collection using questionnaires that are shared online with businesses that use social media. A total of 100 respondents were obtained in the results of the questionnaire for one week. The final result of the calculation that has been done, which of each alternative has a value or score according to the calculation. Tiktok social media alternatives have a value or score of 0.18, Instagram has a value or score of 0.21, Facebook has a value or score of 0.33, and Whatsapp has a value or score of 0.29. Therefore, an alternative end result that is often used in the marketing process through social media in Manokwari is Facebook social media, which has the highest value or score from other social media. From the results of this study it was found that Facebook social media is often used as a marketing medium.